Quality Appraisal of Drinking Water from Bharatpur, Chitwan, Nepal - Khanal, Bipin; Kandel, Krishna Prasad (BMC Journal of Scientific Research, 2025)
In Nepal, underground water is the foundation of drinking water for the mainstream of populations. In this research, a random selection of samples was carried out through selection of 23 underground water samples in Bharatpur from April to May 2024, and the physicochemical parameters were analysed. The physical parameters included total dissolved solids (TDS) and turbidity, while the chemical parameters included alkalinity, hardness, calcium hardness, chloride, iron and sulphate. The results demonstrated that out of 23 water samples, 56.5% exceeded the calcium hardness value set by the WHO drinking water guidelines, and 8.7% exceeded the value set by National Drinking Water Quality Standards (NDWQS). Further, 21.7% samples showed turbidity, higher than the WHO guideline and NDWQS respectively. The highest percentage 60.8%, of the samples exceeded the turbidity and calcium hardness value compared to the guidelines for drinking water quality.